17-(6x+3)-2x+4=

Simple and best practice solution for 17-(6x+3)-2x+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17-(6x+3)-2x+4= equation:


Simplifying
17 + -1(6x + 3) + -2x + 4 = 0

Reorder the terms:
17 + -1(3 + 6x) + -2x + 4 = 0
17 + (3 * -1 + 6x * -1) + -2x + 4 = 0
17 + (-3 + -6x) + -2x + 4 = 0

Reorder the terms:
17 + -3 + 4 + -6x + -2x = 0

Combine like terms: 17 + -3 = 14
14 + 4 + -6x + -2x = 0

Combine like terms: 14 + 4 = 18
18 + -6x + -2x = 0

Combine like terms: -6x + -2x = -8x
18 + -8x = 0

Solving
18 + -8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + -8x = 0 + -18

Combine like terms: 18 + -18 = 0
0 + -8x = 0 + -18
-8x = 0 + -18

Combine like terms: 0 + -18 = -18
-8x = -18

Divide each side by '-8'.
x = 2.25

Simplifying
x = 2.25

See similar equations:

| ((3(x-4)/4)/4)=4x-4 | | 6a^2+27a-15=0 | | 7x+2y=26 | | 75/3*25= | | 10w-14wv-15w+21v=0 | | 3(x-8)=4(x+2) | | -2[6x+1]=4[x-5]-2 | | -12*(6-4)+2= | | (5/8)(-9) | | 3(x-8)=4x+2 | | -12*6-(4+2)= | | 8ax-6x-12a+9=0 | | 16x=1248 | | (-12*6)-4+2= | | 15-2n=n-1 | | 3/4-7/20 | | -7/6=-2n+7/3n | | -12*6-4+2= | | 7/5-3/8k=-2 | | 12(12v+12)-10=2+12v | | 48-6/(3*2)= | | 1/12+x=1/4 | | 48-(6/3)*2= | | (48-6)/3*2= | | 5+-8y=9y+2 | | -3y=-3-x | | 4.5(r-4)=-3(r-1.5) | | .05x+.13(x-3)=.2(x-2) | | 3x-8=6x+1 | | 3h^2+5h/h | | 48-6/3*2=7 | | X^2-2mx+1=0 |

Equations solver categories